2018
DOI: 10.3390/nu10121971
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine-N-oxide (TMAO) as Novel Potential Biomarker of Early Predictors of Metabolic Syndrome

Abstract: There is a mechanistic link between the gut-derived metabolite trimethylamine-N-oxide (TMAO) and obesity-related diseases, suggesting that the TMAO pathway may also be linked to the pathogenesis of obesity. The Visceral Adiposity Index (VAI), a gender-specific indicator of adipose dysfunction, and the Fatty Liver Index (FLI), a predictor of non-alcoholic fatty liver disease (NAFLD), are early predictors of metabolic syndrome (MetS). In this cross-sectional observational study, we investigated TMAO levels in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
173
5
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(181 citation statements)
references
References 55 publications
0
173
5
3
Order By: Relevance
“…Increased TMAO concentration in the current meta‐analysis was associated with increased BMI both in the two‐class meta‐analysis and the dose‐response synthesis. The positive association between obesity and TMAO was shown in several previous studies . In conclusion, in the current meta‐analysis, for the first time, the results of studies investigating the association between circulating TMAO and BMI in a dose‐dependent and two‐class meta‐analysis were summarized.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Increased TMAO concentration in the current meta‐analysis was associated with increased BMI both in the two‐class meta‐analysis and the dose‐response synthesis. The positive association between obesity and TMAO was shown in several previous studies . In conclusion, in the current meta‐analysis, for the first time, the results of studies investigating the association between circulating TMAO and BMI in a dose‐dependent and two‐class meta‐analysis were summarized.…”
Section: Discussionmentioning
confidence: 57%
“…After that dose, the curve is rather slope. Similarly, Barrea et al suggested cut offs of greater than or equal to 8.02 μM and greater than or equal to 8.74 μM for circulating TMAO in prediction of non‐alcoholic fatty liver disease and metabolic syndrome, respectively. In the current meta‐analysis, a positive association between circulating TMAO and BMI in a dose‐dependent manner was confirmed in studies involved apparently healthy individuals ( P nonlinearity = .007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, low TMAO and carnitine status of pregnant women may lead to malnutrition, organ dysfunction, and embryonic development restriction. In addition, TMAO synthesized by the intestinal microbiota has been demonstrated as early predictors of metabolic syndrome, and strong linked with atherosclerosis, type 2 diabetes, vitamin D deficiency and chronic kidney disease [10][11][12]34]. The metabolic syndrome induced by TMAO caused increased sPTB risk [13,14].…”
Section: Discussionmentioning
confidence: 99%